A review on magneto-mechanical characterizations of magnetorheological elastomers. (1st November 2020) - Bastola, Anil K.; Hossain, Mokarram
Abstract: Magnetorheological elastomers (MREs) are a class of recently emerged smart materials whose moduli are largely influenced when exposed to an external magnetic field. The MREs are particulate composites, where micro-sized magnetic particles are dispersed inside a non-magnetic polymeric matrix. These elastomers are known for changing their mechanical and rheological properties in the presence of a magnetic field. This change in properties is widely known as the magnetorheological (MR) effect. The MR effect depends on a number of factors such as type of matrix materials, type, concentration and distribution of magnetic particles, use of additives, working modes, and magnetic field strength. The investigation of MREs' mechanical properties in both off-field and on-field (i.e. absence and presence of a magnetic field) is crucial to deploy them in real engineering applications. The common magneto-mechanical characterization experiments of MREs include static and dynamic compression, tensile, and shear tests in both off-field and on-field. This review article aims to provide a comprehensive overview of the magneto-mechanical characterizations of MREs along with brief coverage of the MRE materials and their fabrication methods.